Seroprevalence of antibodies against smooth Brucella in small ruminants in the states of Sergipe, Bahia, Ceará and Paraíba - Silva, G. C.P. (2022)
Brucellosis is a zoonotic disease widespread almost all over the world, representing a significant economic and public health problem. Brucella melitensis, B. suis and B. abortus are considered the most pathogenic species for humans. The most virulent species, B. melitensis is endemic in many parts of the world, particularly the biovar 3 in the Mediterranean and Eastern Europe. Some Latin American countries are seriously affected by biovar 1, especially Mexico, Peru and northern Argentina. Furthermore, while Brazil is considered free of this etiologic agent, one recurrent question is whether this infection really does not occur in Brazil or there is a lack of research/data on the subject. To answer this question, this study aims to investigate the occurrence of antibodies against smooth Brucella in goats and sheep in the states of Sergipe, Paraíba, Ceará and Paraíba. All samples were screened by the Rose Bengal test (RBT). The complement fixation (CFT) and the fluorescence polarization (FPT) tests were used as confirmatory tests. There were no positive samples in the confirmatory tests (both CFT and FPT). We, therefore, conclude that this result reinforces the previous knowledge regarding the exotic status of B. melitensis infection in Brazil.